Changes of myocardial fibrosis markers with the use of beta-blockers and mineralocorticoid receptor antagonists in patients with heart failure with mid-range ejection fraction of ischemic origin - O. A. Osipova; E. V. Gosteva; T. P. Golivets; O. N. Belousova; O. A. Zemlyansky; M. V. Pokrovsky; A. I. Golovin; N. V. Grigorenko; A. A. Merezhko (Кардиоваскулярная терапия и профилактика, 2021)
Aim. To compare the effect of 12-month pharmacotherapy with a betablocker (BB) (bisoprolol and nebivolol) and a combination of BB with a mineralocorticoid receptor antagonist (bisoprolol+eplerenone, nebivolol+eplerenone) on following fibrosis markers: matrix metalloproteinases 1 and 9 (MMP-1, MMP-9) and tissue inhibitor of MMP-1 (TIMP-1) in patients with heart failure with mid-range ejection fraction (HFmrEF) of ischemic origin.Material and methods. The study included 135 patients, including 40 (29,6%) women and 95 (70,4%) men aged 45-60 years (mean age, 53,1±5,7 years). Patients were randomized into subgroups based on pharmacotherapy with BB (bisoprolol or nebivolol) and their combination with eplerenone. The enzyme-linked immunosorbent assay was used to determine the level of MMP-1, MMP-9, TIMP-1 (ng/ml) using the commercial test system “MMP-1 ELISA”, “MMP-9 ELISA”, “Human TIMP-1 ELISA” (“Bender Medsystems “, Austria).Results. In patients with HFmrEF of ischemic origin, there were following downward changes in serum level of myocardial fibrosis markers, depending on the therapy: bisoprolol  — MMP-1 decreased by 35% (p<0,01), MMP-9  — by 56,3% (p<0,001), TIMP-1  — by 17,9% (p<0,01); nebivolol  — MMP-1 decreased by 45% (p<0,001), MMP-9  — by 57,1% (p<0,001), TIMP-1  — by 30,1% (p<0,01); combination of bisoprolol with eplerenone  — MMP-1 decreased by 43% (p<0,001), MMP-9  — by 51,2% (p<0,001), TIMP-1  — by 25,1% (p<0,01); combination of nebivolol with eplerenone  — MMP-1 decreased by 53% (p<0,001), MMP-9 — by 64,3% (p<0,001), TIMP-1 — by 39% (p<0,01). In patients with NYHA class I HFmrEF after 12-month therapy, the decrease in MMP-1 level was 39,9% (p<0,01), MMP-9  — 57,5% (p<0,001). In class II, the decrease in MMP-1 level was 47% (p<0,001), MMP-9 — 49,7% (p<0,001). A significant decrease in TIMP-1 level was revealed in patients with class I by 29% (p<0,01), in patients with class II by 27,1% (p<0,01) compared with the initial data.Conclusion. A significant decrease in the levels of myocardial fibrosis markers (MMP-1, MMP-9, TIMP-1) was demonstrated in patients with HFmrEF of ischemic origin receiving long-term pharmacotherapy. The most pronounced effect was determined in patients with NYHA class I HF.